2005
DOI: 10.1007/s10552-005-2702-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Plasma Insulin-like Growth Factor-1 and Insulin-like Growth Factor Binding Protein-3: Personal and Lifestyle Factors (United States)

Abstract: Insulin-like growth factors (IGFs) play an important role in cell proliferation and apoptosis, and recent epidemiologic studies have suggested that circulating IGF-1 and IGF binding protein-3 (IGFBP-3) may be related to colorectal, breast, and prostate cancer risk. The purpose of this analysis was to investigate the role of various personal and lifestyle factors in the inter-individual variation of circulating IGF-1 and IGFPB-3. We measured plasma levels of IGF-1 and IGFBP-3 in a sequential sample of 333 popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 66 publications
4
41
2
Order By: Relevance
“…In addition, estrogen may alter colorectal cancer risk directly via estrogen receptors in the colonic mucosa (55). Furthermore, changes in the metabolic profile, specifically in the insulin/IGF axis resulting from excess adipose tissue, may also play a role in increasing colorectal cancer risk (36); estrogen is believed to exert a protective effect through the insulin/IGF axis by reducing serum IGF levels (56). In addition, it should be noted that, among postmenopausal women, adipose tissue is the principal source of endogenous estrogen (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, estrogen may alter colorectal cancer risk directly via estrogen receptors in the colonic mucosa (55). Furthermore, changes in the metabolic profile, specifically in the insulin/IGF axis resulting from excess adipose tissue, may also play a role in increasing colorectal cancer risk (36); estrogen is believed to exert a protective effect through the insulin/IGF axis by reducing serum IGF levels (56). In addition, it should be noted that, among postmenopausal women, adipose tissue is the principal source of endogenous estrogen (37).…”
Section: Discussionmentioning
confidence: 99%
“…Studies among healthy adults have reported a null association (2-4), a positive association (5), an inverse association (6)(7)(8)(9), and a nonlinear association (10,11) between BMI and IGF-I levels. The nonlinear associations were similar to what we observed in Japanese Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, however, have been inconsistent with respect to the relationships between adiposity and circulating levels of IGF proteins (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Studies among healthy adults have reported a null association (2-4), a positive association (5), an inverse association (6)(7)(8)(9), and a nonlinear association (10,11) between body mass index (BMI) and IGF-I levels. We are unaware of any study that has looked at possible ethnic differences in the relationship between obesity and circulating IGF-I, and this may be important in addressing the metabolic basis for ethnic differences in cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Small intervention studies (2,3,4,5,6,7,8,9,10) and large cross-sectional studies (11,12,13,14,15) have demonstrated that oral estrogens reduce serum concentrations of total IGF1. These findings have been observed both in menopausal women and in those with hypopituitarism.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of oral estrogens have provided inconsistent results in relation to IGFBP3 concentrations, with reports of reduced serum levels (5,7,13,22,23) or an absence of effects (2,4,6,12,14,15).…”
Section: Introductionmentioning
confidence: 99%